Introducing Probabilities and Present Value Analysis into Taxation: A Reply. - Crumbley, D. Larry (The Accounting Review, 1973)
Abstract This article presents a reply to the comments made by professor Tsvi Ophir to the author's article on gift tax computation. The author was trying to show that the decision to make a gift is determined by how long the individual is expected to live. It was stated clearly that the property did not appreciate or depreciate during the period of time between the date of gift and date of death of the donor. Thus, in his example the estate tax of $150,000 remained the same whether the individual lived five more years or ten years. What did change, however, was the fact that the taxpayer who elected not to make the gift has the use of the funds in his estate for five additional years. Present value refers to the broad area of time value of money. To be more precise he was attempting to incorporate the concept of time value of money into the problem under consideration. bracket. But the gift tax rate schedule is progressive in nature. As more and more gifts are made, the donor moves into a higher and higher gift tax bracket. After a point the individual's gift tax bracket may become higher than his estate tax bracket.